Evaluation of the efficiency of the shields for reduction of airplane noise effects - Шило, В. Ф.; Картышев, O. A. (Proceedings of National Aviation University (archive), 1999)
Acoustic shield is one of the most effective means for reduction of transport noise effect, aviation included. Noise shields are widely used in world practice. Acoustic efficiency of shields depends on many factors, therefore it is necessary to use, on the designing stage, complicated methodical and computer means for their substantiation